El " cole" en cas@.com (Journal of Parents and Teachers, 2014)
The article highlights the reality of homeschooling and analyzes the reasons that explain this phenomenon. In this way, the author exposes an experience from which the whole article is based. It also highlights the legal aspects of this type of education as well as its limits and risks.
Keywords: Homeschooling; Education System; Debate